Use of scanning electron microscopy for the evaluation of intestinal epithelium integrity - Gomide Junior, Marcio Heber [UNESP]; Sterzo, Elton Vinícius [UNESP]; Macari, Marcos [UNESP]; Boleli, Isabel Cristina [UNESP] (Sociedade Brasileira de Zootecnia, 2004)
Propõe-se, neste trabalho, o uso de microscopia eletrônica de varredura para avaliar perda de epitélio intestinal da mucosa intestinal de pintos machos e fêmeas submetidos a prolongado jejum pós-eclosão de água e ração. Dois segmentos do duodeno, jejuno e íleo por ave foram coletados e processados pelo método de rotina para microscopia eletrônica de varredura. Seis diferentes graus de perda de epitélio intestinal foram determinados: grau 0, vilos normais, sem extrusão; grau 1, vilos com pequenos pontos de extrusão; grau 2, vilos com perda de epitélio no ápice; grau 3, vilos com perda de epitélio na região apical; grau 4, vilos com perda de epitélio em sua metade superior; grau 5: vilos sem epitélio; grau 6: vilo quebrado. As três regiões intestinais das fêmeas apresentaram aproximadamente 90% de seus vilos normais (graus 0 e 1), enquanto nos machos ocorreu 38% de vilos normais no duodeno e jejuno e 85% no íleo. Além disso, machos apresentaram graus mais acentuados de perda de epitélio (graus 3, 4, 5 e 6) que as fêmeas (grau 3). Os dados indicaram que a mucosa intestinal de pintos machos é mais sensível a prolongado jejum pós-eclosão que a de pintos fêmeas. A microscopia eletrônica de varredura pode ser usada como um método de rotina seguro para a caracterização e quantificação de perda de epitélio intestinal.

This work reports the use of scanning electron microscopy to evaluate intestinal epithelium loss in broilers. Intestinal mucosa of male and female chicks submitted to prolonged period post-hatching of water and feed deprivation was evaluated. Two segments of the duodenum, jejunum and ileum were taken per bird, and routinely processed by scanning electron microscopy. Six distinct degrees of epithelium loss were determined: degree 0, normal villi without apparent extrusion; degree 1, villi presenting small areas of epithelium loss; degree 2, villi without epithelium at the apex; degree 3, villi without epithelium at the apical region; degree 4, villi without epithelium in the upper half; degree 5, lack of epithelium in the whole villus; degree 6, loss of villi. Fasted male chicks presented only up to 38% of normal villi (degree 0 and 1) in the duodenum and jejunum, and 85% in the ileum, whereas fasted female chicks presented approximately 92% of normal villi in the three intestinal regions. Besides this, fasted male chicks had more accentuated degrees of epithelium loss (degrees 3, 4, 5 and 6) than females (degree 3). Data indicated that the intestinal mucosa in male chicks presents higher susceptibility to prolonged fasting than in females. Scanning electron microscopy is shown to be a reliable routine technique to characterize and quantify intestinal epithelium loss.
Uso de microscopia eletrônica de varredura para avaliação de integridade do epitélio intestinal
Keywords: Broilers; Fasting; intestinal epithelium loss; Scanning electron microscopy; frangos; Jejum; perda de epitélio intestinal; Microscopia eletronica de varredura